Initial Validation Study for a Scale Used to Determine Service Intensity for Itinerant Teachers of Students with Visual Impairments. (November 2015) - Pogrund, Rona L.; Darst, Shannon; Munro, Michael P.
Introduction: The purpose of this study was to begin validation of a scale that will be used by teachers of students with visual impairments to determine appropriate recommended type and frequency of services for their students based on identified student need. Methods: Validity and reliability of the Visual Impairment Scale of Service Intensity of Texas (VISSIT) were evaluated using a mixed-methods survey research design. Participants used the VISSIT to determine services for at least one student and then completed an electronic survey regarding the use of the tool. Results: Twenty-five participants completed at least one VISSIT and completed the electronic survey. Social validity was supported by 92% of the participants stating that the tool was easy to use as a way to determine service time and was also supported by 96% of the participants stating that they would use the VISSIT for determining the type and amount of service recommended for their students. Consequential validity was supported by 71% of the participants stating that the tool's results matched their professional judgment regarding student need and recommended service time and was also supported by 75% of the participants stating that the tool's results directly translated into type and amount of service they would recommend. Internal consistency reliability was demonstrated by the result of a factor analysis of Cronbach's Alpha statistic of .747 for the entire set of VISSIT items. Discussion: The results demonstrate that the VISSIT is a moderately valid and reliable tool for helping teachers of students with visual impairments determine the type and amount of visual impairment services based on individual student need. Implications for practitioners: The VISSIT is a tool that itinerant teachers of students with visual impairments can use to determine the appropriate amount of service for all students on their caseloads and offers a more objective way to recommend service intensity based on student need.